When crust comes of age: on the chemical evolution of Archaean, felsic continental crust by crustal drip tectonics - Nebel, O. (Philos Trans A Math Phys Eng Sci, 2018)
The secular evolution of the Earth's crust is marked by a profound change in average crustal chemistry between 3.2 and 2.5 Ga. A key marker for this change is the transition from Archaean sodic granitoid intrusions of the tonalite–trondhjemite–granodiorite (TTG) series to potassic (K) granitic suites, akin (but not identical) to I-type granites that today are associated with subduction zones. It remains poorly constrained as to how and why this change was initiated and if it holds clues about the geodynamic transition from a pre-plate tectonic mode, often referred to as stagnant lid, to mobile plate tectonics. Here, we combine a series of proposed mechanisms for Archaean crustal geodynamics in a single model to explain the observed change in granitoid chemistry. Numeric modelling indicates that upper mantle convection drives crustal flow and subsidence, leading to profound diversity in lithospheric thickness with thin versus thick proto-plates. When convecting asthenospheric mantle interacts with lower lithosphere, scattered crustal drips are created. Under increasing P-T conditions, partial melting of hydrated meta-basalt within these drips produces felsic melts that intrude the overlying crust to form TTG. Dome structures, in which these melts can be preserved, are a positive diapiric expression of these negative drips. Transitional TTG with elevated K mark a second evolutionary stage, and are blends of subsided and remelted older TTG forming K-rich melts and new TTG melts. Ascending TTG-derived melts from asymmetric drips interact with the asthenospheric mantle to form hot, high-Mg sanukitoid. These melts are small in volume, predominantly underplated, and their heat triggered melting of lower crustal successions to form higher-K granites. Importantly, this evolution operates as a disseminated process in space and time over hundreds of millions of years (greater than 200 Ma) in all cratons. This focused ageing of the crust implies that compiled geochemical data can only broadly reflect geodynamic changes on a global or even craton-wide scale. The observed change in crustal chemistry does mark the lead up to but not the initiation of modern-style subduction. This article is part of a discussion meeting issue ‘Earth dynamics and the development of plate tectonics’.